2019
DOI: 10.1111/jam.14183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage temperature on bacterial diversity in chicken skin

Abstract: Aims The purpose of this experiment was to study the bacterial diversity and predominance of spoilage bacteria in chicken skin at different storage temperatures (4, 25 and 37°C). Methods and Results The total bacteria in chicken skin were collected, total DNA was extracted by an E. Z. N. A. Bacterial DNA Kit, and the v3–v4 regions of the 16S rDNA gene in the microbiota of the chicken skin were studied using the Illumina Hiseq platform. A total of 91 862 bacterial sequences were obtained for assessing the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Proteobacteria was the dominant phylum in our study among the 38 different phyla, corroborating previous studies reporting Proteobacteria as the most abundant bacterial phylum in chicken carcasses, regardless the sampling point in the slaughter plant ( Handley et al, 2018 ) or storage temperature of chicken carcasses ( Meng et al, 2019 ). Within Gammaproteobacteria, the most abundant bacterial class detected in our study, we observed dominance of Pseudomonadaceae and Moraxellaceae families.…”
Section: Discussionsupporting
confidence: 91%
“…Proteobacteria was the dominant phylum in our study among the 38 different phyla, corroborating previous studies reporting Proteobacteria as the most abundant bacterial phylum in chicken carcasses, regardless the sampling point in the slaughter plant ( Handley et al, 2018 ) or storage temperature of chicken carcasses ( Meng et al, 2019 ). Within Gammaproteobacteria, the most abundant bacterial class detected in our study, we observed dominance of Pseudomonadaceae and Moraxellaceae families.…”
Section: Discussionsupporting
confidence: 91%
“…Rarefaction analysis of each sample resulted in curves close to the platform stage in Fig. 1, indicating that the sequencing quantity well reflected the bacterial community structure and diversity in the samples (Gu et al 2018; Meng et al 2019).…”
Section: Resultsmentioning
confidence: 79%
“…However, during industrial production, chilled meat is susceptible to microbial contamination due to its high water activity and nutrient-rich composition. This can lead to shortened shelf life and potential food safety risks [2].…”
Section: Introductionmentioning
confidence: 99%